Surf's up Geronimo - Stilton, Geronimo (New Delhi Scholastic, 2025)
Blue skies and sandy beaches? I was dreaming of a nice quiet vacation in the sun. I needed to getaway from the rat race for a while and without Thea and Trap to drag me on some crazy adventure I'd be able to relax for once. But instead of a beautiful seaside resort, I found myself staying at a fleabag hotel that was falling down around my ears! Oh-would I ever be able to enjoy my vacation?
Keywords: Children Fiction